Kesadaran Keagamaan dan Harmoni Sosial Muslim Plateau Dieng - Angga Teguh Prastyo (At-Tafkir, 2022)
This research was conducted to describe in an actual and informative manner the religious awareness and social harmony of the Dieng Plateau community, in the mind of the turmoil of identity and issues of religious and cultural relations which at any time there are parties who impose it as an endless conflict. This article explains the study of religion and a culture that builds social awareness and harmony in the Dieng Plateau community in respecting plurality and diversity. The research method used is descriptive qualitative. Data collection techniques using interviews, documentation and observation. Meanwhile, data analysis used flow stages: 1) data reduction, 2) data display, 3) conclusion verification. This study concludes that religious awareness and social harmony are a way of life and not just religious expressions of the Dieng Plateau community. Religious awareness and social harmony provide insight into a society that maintains a balanced relationship between religion and culture as a guardian and preservation of the values of Islamic cosmopolitanism. This confirms that religious awareness and social harmony are attitudes and behaviors to create Islamic cosmopolitanism towards people of other religions and in a pluralistic society.